One mutation away, the potential zoonotic threat - NeoCoV, planetary health impacts and the call for sustainability - Hana Chen Wei Jun; Roy Rillera Marzo; Tang Hooi Chia; Saeid Mezail Mawazi; Mohammad Yasir Essar (SAGE Publishing, 2022)
A recent study entitled "Close relatives of MERS-CoV in bats use ACE2 as their functional receptors" posted on the bioRxiv preprint server has identified two close relatives of the Middle East Respiratory Syndrome coronavirus (MERS-CoV) in South African bats - NeoCoV and PDF-2180-CoV which can efficiently use Angiotensin-converting enzyme 2 (ACE2) in bats but less so in humans. However, researchers suggested that NeoCoV could be infectious to humans via one key mutation - T510F mutation on the receptor-binding motif. As suggested that the origin of MERSCoV might be a result of intra-spike recombination between a NeoCoV-like virus and a DPP4-using virus, the nonhuman infectious NeoCoV firstly identified in 2011 is seen as a time boom,1 and this alarms the zoonotic potential of possible "MERS-CoV-2" using ACE2 in the future. As coronavirus outbreak is part of human causes of global change,2 recommendations are no longer limited to be preventive, but instead, sustainability should be planned to safeguard planetary health.